What moves the Beveridge curve and the Phillips curve: An agent-based analysis - Siyan Chen; Saul Desiderio (Kiel Institute for the World Economy (IfW), 2017)
Understanding what moves the Phillips curve is important to monetary policy. Because the Phillips curve has experienced over time movements similar to those characterizing the Beveridge curve, the authors jointly analyze the two phenomena. They do that through an agent-based macro model based on adaptive micro-foundations, which works fairly well in replicating a number of stylized facts, including the Beveridge curve, the Phillips curve and the Okun curve. By Monte Carlo experiments the authors explore the mechanisms behind the movements of the Beveridge curve and the Phillips curve. They discovered that shifts of the Beveridge curve are best explained by the intensity of worker reallocation. Reallocation also shifts the Phillips curve in the same direction, suggesting that it may be the reason behind the similarity of the patterns historically recorded for these two curves. This finding may shed new light on what moves the Phillips curve and might have direct implications for the conduction of monetary policy.
Keywords: C63; D51; E31; J30; J63; J64; 330; Beveridge curve; Phillips curve; labor market dynamics; agent-based simulations; sensitivity analysis